2012
DOI: 10.1159/000339755
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling Identifies Haptoglobin as a Potential Serum Biomarker for Steroid-Resistant Nephrotic Syndrome

Abstract: <b><i>Background:</i></b> Long-term outcomes for patients with adult idiopathic nephrotic syndrome correlate closely with steroid responsiveness. The aim of this prospective study was to evaluate the difference in serum proteomes between steroid-sensitive nephrotic syndrome (SSNS) and steroid-resistant nephrotic syndrome (SRNS) patients and identify potential biomarkers for the prediction of SRNS. <b><i>Methods:</i></b> We performed a gel-based proteomic study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…This was similar to the findings that an unknown protein spot identified as haptoglobin in patient sera using the mass spectra strategy (26)(27)(28). For further verification of the mass spectra results, western blotting was used (29), and the results demonstrated that haptoglobin protein was specificity connected with rabbit anti-human-haptoglobin. Therefore, it was concluded that the P43 protein was haptoglobin.…”
Section: Discussionsupporting
confidence: 84%
“…This was similar to the findings that an unknown protein spot identified as haptoglobin in patient sera using the mass spectra strategy (26)(27)(28). For further verification of the mass spectra results, western blotting was used (29), and the results demonstrated that haptoglobin protein was specificity connected with rabbit anti-human-haptoglobin. Therefore, it was concluded that the P43 protein was haptoglobin.…”
Section: Discussionsupporting
confidence: 84%
“…Wen et al reported markedly elevated levels of haptoglobin in the serum of patients with SRNS, compared to SSNS [15]. In a recent uncontrolled study on a 38 patients with FSGS, fractional excretion of IgG was an independent predictor of remission, and urinary alpha 2-macroglobulin/Cr was a strong predictor of end stage renal disease [16].…”
Section: Discussionmentioning
confidence: 98%
“…For instance, a pharmacological predictive biomarker has been reported in idiopathic nephrotic syndrome, a RD affecting the kidneys. Specifically, Wen et al [47] found a significant difference in the serum proteome of steroid-sensitive nephrotic syndrome (SSNS) and steroid-resistant nephrotic syndrome (SRNS, OMIM 256370) patients, predictive of their respective responses to treatment.…”
Section: Predictive/therapeutic Biomarkermentioning
confidence: 99%